Development of stable and high-performance polyaniline activated carbon electrodes for capacitive deionization desalination - Barcelos, Kamilla Malverdi (Universidade Federal de São Carlos, 2021)
Capacitive deionization (CDI) emerged as a cost-effective alternative for the desalination of brackish water (salt concentration lower than 10 g L−1). Significant progress in electrode materials in terms of salt adsorption capacity (SAC) and charge efficiency (QE) has been performed in the last few years. However, there are still challenging issues concerning the improvements of the adsorption/desorption kinetics and the electrode stability for long-term operation. In this sense, the main goal of this thesis was the development of stable electrodes of polyaniline (PAni)-activated carbons (PAC) for long-term desalination, with optimized electrosorption/desorption kinetics. The comparison between blade-casting (DB) and free-standing (FS) electrodes of p-toluenesulfonate-doped PAC (PAC/PTS) showed the effects of electrode interparticle porosity and thickness on their textural and electrochemical properties and enabled a better understanding of how tuning the preparation technique of the CDI electrodes can improve the desalination performance, especially in terms of adsorption/desorption kinetics. Although the different electrodes perform similarly in terms of gravimetric salt adsorption capacities, FS electrodes outperform the DB electrodes in terms of volumetric salt adsorption capacities. These carbon films were more compact, and a large quantity of electroactive material was available for salt adsorption. Therefore, if the material cost is not a limitation, the maximum amount of salt could be removed using compact CDI cells with FS electrodes. On the other hand, when the electrosorption and desorption kinetics are considered, the DB electrode presented superior performance, mainly due to its higher interparticle porosity that minimizes the distance of ion diffusion from the bulk solution to the inner surface, thus facilitating the access of the ions to the micropores. These results demonstrated that the faster kinetics provided by enhanced mass transfer in thin electrodes with high interparticle porosity can be decisive for the selection of the best electrode in CDI applications, specially aiming for future applications in flow-through CDI cells. Sequentially, different strategies were studied in order to optimize the desalination performance and the long-term operation stability of PAC/PTS electrodes. Additionally, the new sulfate-doped PAni-activated carbon (PAC/S) was proposed to investigate the influence of chemical and textural properties of the electrodes on the desalination stability. Chemical treatments with ethylenediamine and (3-aminopropyl)triethoxysilane were used to change the chemical surface groups and the potentials of zero charge (EPZC) to more negative values of the materials and promote asymmetry between the electrodes. Symmetric and membrane CDI (MCDI) configurations were also investigated for performance comparison. The control of the potential distribution in asymmetric cells was pointed out as an effective strategy to suppress the carbon oxidation reactions responsible for the SAC loss and improve the long-term stability. However, the best performance and long-term stability were achieved using PAC/PTS electrodes in the MCDI configuration. The use of ion-exchange membranes (IEM) had proved to be a feasible method to improve the electrosorption capacity by reducing the effect of co-ion expulsion and inhibit the faradaic reactions by limiting the transport of the electrochemically active species across the IEM. For this cell configuration, a remarkable value of SAC (~32 mg g-1 at 1.2 V), along with 100% of performance retention was observed over 100 cycles. Our findings enable a better understanding of how to mitigate faradaic reactions and improve the long-term stability of PAC electrodes, thus providing promising electrodes for large-scale CDI applications.
Desenvolvimento de eletrodos de carvão ativado de polianilina estáveis e de alta performance para dessalinização por deionização capacitiva
Keywords: Dessalinização da água; Deionização capacitiva; Carvão ativado de polianilina; Water desalination; Capacitive deionization; Polyaniline-activated carbon; ENGENHARIAS::ENGENHARIA QUIMICA